Analisis Wanprestasi dalam Penggunaan TikTok PayLater menurut perspektif UUPK 1999 dan Hukum Perdata - Putri Ayudhiya, Rubila; Syuhada, Otong; Pribadi, Riky (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
Technological developments are increasing, one of which is marked by the existence of e-commerce and fintech to facilitate transactions for the public. In this modern era, people are more interested in online transactions such as buying and selling. TikTok Shop is one of the applications widely used by Indonesians. One of the payment methods on TikTok Shop is TikTok PayLater. This study uses an empirical juridical research method, which examines the applicable legal provisions and what actually happens in society. This study uses a qualitative approach based on a review of the PayLater contract, interest structure, administration fees, and late payment penalties. The data collection technique in this study was obtained through interviews with seven informants who are active users of TikTok PayLater. The results of the study show that the TikTok PayLater agreement is legally valid because it complies with Article 1320 of the Civil Code and is recognised by the ITE Law. The TikTok PayLater agreement includes a standard agreement, the content of which is still limited by the provisions of Article 18 of Law 1999. However, in practice, it still has the potential to cause disputes due to default as regulated in Article 1243 of the Civil Code. However, such collection practices violate Article 4 of the 1999 Consumer Protection Law as they infringe upon consumers' rights to comfort and security. Therefore, the use of TikTok PayLater requires responsibility from both parties.